2015
DOI: 10.1136/bmjquality.u205401.w3279
|View full text |Cite
|
Sign up to set email alerts
|

Performance improvement initiative: prevention of surgical site infection (SSI)

Abstract: Mafraq Hospital performs an average of 10,000 surgeries every year. The impact of having high volume high risk surgical procedures calls for the need to ensure safe surgery and a prevention of surgical site infection (SSI). SSI represents a significant portion of healthcare-associated infections (HAIs). The impact on morbidity, mortality, and cost of care has resulted in identifying the need to reduce SSI as a top priority to prevent healthcare associated infections. The good news is that the majority of SSIs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Various preventive managements, including perioperative antibiotics, mechanical bowel preparation, hand scrub, skin preparation with antiseptic agents, mechanical barrier film and irrigation of the surgical site, have been tested. As it is well known that a patient's skin is a major source of pathogens, preoperative skin preparation with antiseptic agents is important for decreasing the risk of postoperative SSI.…”
Section: Introductionmentioning
confidence: 99%
“…Various preventive managements, including perioperative antibiotics, mechanical bowel preparation, hand scrub, skin preparation with antiseptic agents, mechanical barrier film and irrigation of the surgical site, have been tested. As it is well known that a patient's skin is a major source of pathogens, preoperative skin preparation with antiseptic agents is important for decreasing the risk of postoperative SSI.…”
Section: Introductionmentioning
confidence: 99%
“…Although several previous studies related to ICTR have been conducted, these studies investigated the benefits of incorporating leadership rounding into infection prevention and focused on the association between infection control activities with rounding and one specific type of infection [2,[4][5][6][7][8]. These assessments indicated that ICTR was successful in the studied context; nonetheless, these studies lack a comprehensive perspective on the mechanisms of rounding.…”
Section: Discussionmentioning
confidence: 99%
“…The following nine categories of infection control and prevention items were included: (1) hand hygiene (8 items); (2) safety injection practice (9 items); (3) isolation (10 items); (4) strategies to prevent occupationally acquired infections (6 items); (5) practices to prevent catheter-related (central, urine catheter), surgical site infection and pneumonia (16 items); (6) decontamination, disinfection, and sterilization (19 items); (7) linen and laundry management (6 items); (8) environmental prevention of infection (8 items); and (9) maintaining negative/positive pressure (3 items) as shown in Supplemental Table 1 [6].…”
Section: Methodsmentioning
confidence: 99%
“…Although several previous studies related to ICTR have been conducted, these studies investigated the bene ts of incorporating leadership rounding into infection prevention and focused on the association between infection control activities with rounding and one speci c type of infection. 2,4,5,6,8,9 These assessments indicated that ICTR was successful in the studied context; nonetheless, these studies lack a comprehensive perspective on the mechanisms of rounding. In contrast, our study evaluated monitoring of infection control activities based on the entire infection prevention protocol, with a grade-based assessment of infection control activities.…”
Section: Discussionmentioning
confidence: 99%